Responses of headwater lakes to air pollution changes in Finland - Mannio, Jaakko (Finnish Environment Institute, 2013)
The present work provides a national scale assessment of the trace metal contamination of small headwater lakes and the recent development of acidified lakes in Finland. The information is needed as a scientific basis for further actions in air pollution policy. The study is based on observations in a national monitoring network of lake acidification.Anthropogenic, atmospheric deposition is primarily responsible for the increase of Cd, Hg, Pb and As in headwater lake sediments. However, a decline of 20 to 40% of the accumulation of these elements within the last decades was observed, indicating a relatively fast response to the decline in the atmospheric deposition, and that the accumulated stores of atmospheric trace metals in the catchment soils are not dominating the supply of trace elements to lakes.Lake waters reflected atmospheric trace metal pollution as well, but it was not as clearly quantifiable. Acidity controls in particular the level of Cd and Zn, while organic matter (humus) controls more the level of Cr, Fe, Cu and Ni in headwater lakes. Lead, Mn and Al concentrations are affected by both these factors. Humus acts as a carrier for trace metals from catchments soils to surface waters, irrespectively of their original source.Based on comparable chemical data sets, the risks of biological effects in lakes due to trace metals are lower in Finland than in Sweden and Norway. Trace metal levels in lake waters are less critical for the biota than acidity and inorganic (labile) aluminium levels.Due to acidification, there where estimated to be 2200-4400 damaged fish populations in southern and central Finland. Most of these populations are roach in lakes smaller than ten hectares. Sulphate concentrations have declined in all types of small lakes throughout Finland in the 1990s, indicating a clear response to the sulphur emission reductions. Base cation concentrations are still declining in lakes especially in southern Finland, but to a lesser extent than sulphate.There are presently no indications of ...